(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cloud computing facilitates multi-tenancy for optimal resource utilization through leveraging hardware and software resources through multiple clients. Multi-tenant programs operating on a cloud infrastructure are delivered over the network to clients as Software-as - a-Service (SaaS). Multi-tenancy presents additional challenges regarding its benefits, such as partitioning, extensibility and customizability during application development. In this article, we discussed the various types of multi-tenancy, multi-tenancy implementations, advantages, and drawbacks within different cloud-based service models. Many users are, however, reluctant to subscribe to cloud computing services due to security concerns.